The Influence Of Employee Experience Factors On Employee Performance With Mediation Job Satisfaction Of Generation Z Employees At Companies In East Java - Delia Dwi Nanda; Tjahjani Prawitowati (UNIVED Press, 2025)
This research is based on the importance of understanding employee experience in improving employee performance, especially in the era of globalization involving generation Z who have different expectations and preferences in the world of work. The purpose of this study was to test and analyze the influence of employee experience factors on employee performance with job satisfaction mediation. In this study, research data were obtained from 207 respondents using a questionnaire and Likert scale measurement. The data analysis technique used is SEM-Partial Least Square (PLS) to test the hypothesis that has been formulated. The results of this study indicate that the physical environment, cultural environment, and cultural environment have a significant positive effect on employee performance mediated by job satisfaction of generation Z employees at companies in East Java partially. As well as a good physical environment, inclusive organizational culture, and technological support.